2018
DOI: 10.1029/2017je005478
|View full text |Cite
|
Sign up to set email alerts
|

A Field Guide to Finding Fossils on Mars

Abstract: The Martian surface is cold, dry, exposed to biologically harmful radiation and apparently barren today. Nevertheless, there is clear geological evidence for warmer, wetter intervals in the past that could have supported life at or near the surface. This evidence has motivated National Aeronautics and Space Administration and European Space Agency to prioritize the search for any remains or traces of organisms from early Mars in forthcoming missions. Informed by (1) stratigraphic, mineralogical and geochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 410 publications
1
101
0
Order By: Relevance
“…In fact, some evidence suggest that conditions were favourable for life to exist on Mars during the Noachian (~4.1 to 3.7 Ga), from both the standpoints of liquid water availability and metabolic energy sources (Grotzinger et al, 2014;Kral et al, 2014). Following previous successful missions that visited the red planet, upcoming exploration of Mars aims at identifying potential fossilised biosignatures (Mustard et al, 2013;Westall et al, 2015;Vago et al, 2017), with organic carbon obviously constituting the grail to be sought after (Summons et al, 2008;McMahon et al, 2018). To date, although macromolecular carbon has been detected within most of the martian meteorites (Steele et al, 2016(Steele et al, , 2018, only small organic molecules including aromatic, aliphatic, chlorine-and sulfur-rich organic compounds have been measured on Mars (Biemann et al, 1977;Freissinet et al, 2015;Eigenbrode et al, 2018).…”
Section: Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some evidence suggest that conditions were favourable for life to exist on Mars during the Noachian (~4.1 to 3.7 Ga), from both the standpoints of liquid water availability and metabolic energy sources (Grotzinger et al, 2014;Kral et al, 2014). Following previous successful missions that visited the red planet, upcoming exploration of Mars aims at identifying potential fossilised biosignatures (Mustard et al, 2013;Westall et al, 2015;Vago et al, 2017), with organic carbon obviously constituting the grail to be sought after (Summons et al, 2008;McMahon et al, 2018). To date, although macromolecular carbon has been detected within most of the martian meteorites (Steele et al, 2016(Steele et al, , 2018, only small organic molecules including aromatic, aliphatic, chlorine-and sulfur-rich organic compounds have been measured on Mars (Biemann et al, 1977;Freissinet et al, 2015;Eigenbrode et al, 2018).…”
Section: Lettermentioning
confidence: 99%
“…In the context of the massive international push for the astrobiological exploration of Mars, the forthcoming ExoMars and Mars2020 missions will explore the subsurface of ancient (>3.7 Ga) clay-rich martian terrains that likely formed in the presence of water (Ehlmann et al, 2008;Mustard et al, 2013;Westall et al, 2015;Vago et al, 2017). Clay minerals, and smectites in particular, are the prime target of these missions because of their strong absorption capacity, low reactivity, and low permeability when compacted (Kennedy et al, 2002;Naimark et al, 2016;McMahon et al, 2018), giving them a high 'potential of biopreservation'. The presence of these minerals at landing sites is thus believed to maximise the chances of detecting diagnostic organic molecules.…”
Section: Lettermentioning
confidence: 99%
“…Basaltic aquifers on Earth host lithoautotrophic microbial ecosystems fueled by H 2 (an electron donor) generated by serpentinization, an abiotic water–rock reaction known to have taken place in martian history . The possibility of a fossil deep biosphere on Mars is of urgent interest, given the imminence of major NASA and European rover missions explicitly designed to seek evidence of ancient life there . Encouragingly, many of the putative fossil assemblages summarized in the present article were found in basaltic rocks similar to those found on Mars.…”
Section: Major Challenges For Subsurface Palaeobiologymentioning
confidence: 73%
“…Fungi are a complex (eukaryotic) form of life that appeared relatively late in Earth history . Organisms sustained by lithoautotrophic metabolic strategies plausible for hypothetical life on Mars (e.g., methanogenesis; nitrate‐dependent iron oxidation) are abundant in Earth's deep biosphere, but it has not been demonstrated that any of the candidate fossils from the deep biosphere represent such organisms, although some rather unusual examples might conceivably do so . More work is needed, in particular, to search for and characterize definitively prokaryotic fossil remains from the basalt‐hosted deep biosphere.…”
Section: Major Challenges For Subsurface Palaeobiologymentioning
confidence: 99%
“…In 2020, the European Space Agency (ESA) and the Russian Space Agency (Roscosmos) will deliver the ExoMars rover Rosalind Franklin and surface platform to the surface of Mars, whose communications with Earth will be supported by the already operational ExoMars Trace Gas Orbiter (TGO). The ExoMars rover Pasteur payload (Barnes et al, ; Vago et al, ) contains a suite of nine instruments plus a subsurface drill, which will be used to address ExoMars' primary objective of detecting evidence of extinct life within subsurface deposits (McMahon et al, ; Vago et al, ). Among these are a number of imaging instruments, including the Panoramic Camera (PanCam) (Coates et al, ) and the CLose UP Imager (CLUPI) (Josset et al, ), with point hyperspectral data provided by the Infrared Spectrometer for ExoMars (ISEM) (Korablev et al, ).…”
Section: Introductionmentioning
confidence: 99%